Spectrographic analysis of "hoarseness" - Bhat KHV (Journal of All India Institute of Speech and Hearing, 1970)
There is no satisfactory definition for the term hoarseness. Acoustically, hoarseness has been said to be a combination ofbreathy and harsh voice. It is apparent that hoarseness is a complex concept and probably not fully accountable on anyone perceptual dimension. Hence this study was an attempt to reduce the confusion involved in the term "hoarseness" by seeking quantitative" measurement of hoarseness of voice.